2016
DOI: 10.3389/fpls.2016.01484
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Molecular Changes of the Phenylpropanoid Pathway in Tomato (Solanum lycopersicum) Lines Carrying Different Solanum pennellii Wild Chromosomal Regions

Abstract: Solanum lycopersicum represents an important dietary source of bioactive compounds including the antioxidants flavonoids and phenolic acids. We previously identified two genotypes (IL7-3 and IL12-4) carrying loci from the wild species Solanum pennellii, which increased antioxidants in the fruit. Successively, these lines were crossed and two genotypes carrying both introgressions at the homozygous condition (DHO88 and DHO88-SL) were selected. The amount of total antioxidant compounds was increased in DHOs comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Similarly, the genes coding for the transcription factors WD40 and bHLH showed a reduction of the mRNA levels in IL12-4SL vs M82 (3-fold and 2-fold, respectively). These results were in line with those previously obtained in the parental line IL12-4 19 . The expression of the genes coding for the two MYBs showed an opposite trend compared to the structural gene Z-ISO (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, the genes coding for the transcription factors WD40 and bHLH showed a reduction of the mRNA levels in IL12-4SL vs M82 (3-fold and 2-fold, respectively). These results were in line with those previously obtained in the parental line IL12-4 19 . The expression of the genes coding for the two MYBs showed an opposite trend compared to the structural gene Z-ISO (Fig.…”
Section: Resultssupporting
confidence: 93%
“…pennellii subline IL12-4SL. IL12-4SL was previously obtained in our laboratory using the introgression line IL12-4, carrying a QTL (lyc12.1) controlling lycopene accumulation 14,19 . We found that, compared to the parental cultivated line M82, IL12-4SL shows the phenotype already observed in IL12-4 by Rigano et al .…”
Section: Discussionmentioning
confidence: 99%
“…The pathways of fatty acid biosynthesis and starch and sucrose metabolism were also observed, where sugars are important to promote cell growth and to control fruit metabolism during development [34]. Additionally, the phenylpropanoid biosynthesis pathway was also represented, where the secondary metabolites act as antioxidants and in tomato fruit are involved in pigmentation and aroma [35].…”
Section: Discussionmentioning
confidence: 99%
“…139 Four isoforms of 4CL have been iden-tied in Morus notabilis (mulberry) 140 and Arabidopsis. 141 The subcellular localization of specic isoforms of 4CL plays a central role in redirecting the biosynthetic pathway either towards the p-coumaroyl-CoA or towards other branch points in the phenylpropanoid pathway. 141 The conversion of p-coumaroyl-CoA to 5-CQA involves the enzymes hydroxycinnamoyl CoA:quinate hydroxycinnamoyl transferase (HQT) and a cytochrome P450 oxidase p-coumaroyl-3 0 -hydroxylase (C3H) (Fig.…”
Section: Biosynthesis Of Acyl-quinic Acidsmentioning
confidence: 99%